Renal Outcome and New-Onset Renal and Extrarenal Dissections in Patients With Nontrauma Renal Artery Dissection Associated With Renal Infarction. Issue 1 (July 2021) - Faucon, Anne-Laure; Bobrie, Guillaume; Azarine, Arshid; Mousseaux, Elie; Mirault, Tristan; Lorthioir, Aurélien; Azizi, Michel; Amar, Laurence
Abstract : We aimed to compare the characteristics of the patients with renal infarction related to nontrauma renal artery dissection (RAD) with versus without an underlying vascular disease and report long-term renal and vascular outcomes, as well as new-onset renal and extra-RADs. Data from 72 consecutive patients with RAD referred to our Hypertension Unit between 2000 and 2015 were analyzed. Radiological data, including a systematic brain-to-pelvis computed tomography angiography, were independently reviewed. Three main causes of RAD were identified at the initial work-up: fibromuscular dysplasia (n=16); dissecting or aneurysmal multisite arterial disease (n=21) not linked to any known vascular disease; and isolated RAD (n=24) without any other arterial lesion. At diagnosis, patients (median age 46 [interquartile range, 40–53] years, 70.5% males, 26.2% preexisting hypertension, 65.6% smokers) had a median blood pressure of 138 (125–152)/87 (78–97) mm Hg. Estimated glomerular filtration rate was 81 (66–95) mL/min per 1.73 m 2 and 18% had renal impairment. Patients were treated with antiplatelet drugs (65.6%), anticoagulant (3.3%). A total of 11.5% underwent angioplasty. No clinical or biological difference was observed between the 3 groups. After 51 (19–92) months follow-up, blood pressure was reduced by 13 (0–29)/9 (3–18) mm Hg; 11.5% of patients had estimated glomerular filtration rate <60 mL/min per 1.73 m 2 . RAD evolved toward healing (67.2%), aneurysmal dilation (24.6%), or stenosis (8.2%). New-onset RAD was as frequent in dissecting or aneurysmal multisite arterial disease (23.8%) than in fibromuscular dysplasia (25%) group, whereas de novo extrarenal dissection was 6-fold more frequent in dissecting or aneurysmal multisite arterial disease (38.1%) than in fibromuscular dysplasia (6.3%) group. No new event occurred in patients with an initial diagnosis of isolated RAD. Initial diagnostic accuracy using thorough systematic exhaustive explorations of arterial sites helps to stratify the risk of new-onset dissection and adapt monitoring accordingly. Abstract : Supplemental Digital Content is available in the text.